Kematangan Karir pada Siswa Kelas XII SMK Negeri 1 Lobalain Kabupaten Rote Ndao (Study Deskriptif) - Bailao, Viktor; Saba, Khetye Romelya; Indrawan, Putu Agus (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
Vocational students must be mature or really ready to enter a job or college, but there are many students who are confused about the job they want to apply for or are confused about choosing a college. This makes students confused and tends to be immature in the career choices of students. Therefore, this study aims to determine the description of career maturity in class XII students of SMK Negeri 1 Lobalain in the 2023/2024 school year. This research was conducted in the even semester, on March 02, 2024 at SMK Negeri 1 Lobalain. This type of research is using survey research. The population used in this study were all XII grade students of SMK Negeri 1 Lobalain in the 2023/2024 school year, totaling 259 students. The data collection technique in this study used a career maturity questionnaire. The data analysis technique uses descriptive statistical analysis, namely standard deviation, interval class and percentage. The results showed that the career maturity of students was in the mature category with a percentage (69%) which showed that students were quite capable of entering the world of work or being able to compete in college after students completed their education at SMK. This is measured by aspects of career maturity. Career planning, career exploration, decision making, world of work information, and knowledge of occupations of interest.